To find the solutions to the system of equations \( y = x^2 - x - 40 \) and \( y = -3x - 5 \) using the substitution method, we can set the two equations equal to each other since they both equal \( y \).
- Set the equations equal to each other:
\[ x^2 - x - 40 = -3x - 5 \]
- Rearranging the equation gives:
\[ x^2 - x + 3x - 40 + 5 = 0 \]
\[ x^2 + 2x - 35 = 0 \]
- Now, we will factor the quadratic:
\[ (x + 7)(x - 5) = 0 \]
- Setting each factor to zero gives:
\[ x + 7 = 0 \implies x = -7 \]
\[ x - 5 = 0 \implies x = 5 \]
- Now substitute these \( x \) values back into one of the original equations to find the corresponding \( y \) values. We can use \( y = -3x - 5 \):
- For \( x = -7 \):
\[ y = -3(-7) - 5 = 21 - 5 = 16 \] So, one solution is \( (-7, 16) \).
- For \( x = 5 \):
\[ y = -3(5) - 5 = -15 - 5 = -20 \] So, another solution is \( (5, -20) \).
- Thus, the solutions to the system are:
\[ (-7, 16) \text{ and } (5, -20) \]
Therefore, the correct responses are \( (5, -20) \) and \( (-7, 16) \).